Meningkatkan Keterampilan Pemasaran Bagi Pedagang Pasar Tradisional - Kembang, Lale Puspita; Kalbuadi, Amiruddin (Penerbit Widina, Widina Media Utama, 2024)
This article discusses a community service program that focuses on improving marketing skills for traditional market traders to strengthen their competitiveness in modern markets. This program includes training in marketing techniques, product styling, and using social media for promotion. Service activities were carried out at the traditional market in Telaga Waru Village, West Lombok, using observation and in-depth interview methods to evaluate the program's impact on participating traders. The service results show that this training increased traders' understanding and skills in implementing more effective marketing strategies. Significant changes can be seen in more attractive product arrangements, increased promotional activities via social media, and an increase in the number of customers and sales. Apart from that, this program has also increased traders' awareness of the importance of adapting to technological developments in marketing. The conclusion of this service emphasizes the need for continuous training and support from the government and related institutions to maintain the sustainability and competitiveness of traditional markets. Recommendations include developing more comprehensive training programs, providing access to digital resources, and collaborating with various parties to support the sustainability of this initiative.ABSTRAKArtikel ini membahas program pengabdian masyarakat yang berfokus pada peningkatan keterampilan pemasaran bagi pedagang pasar tradisional untuk memperkuat daya saing mereka terhadap pasar modern. Program ini mencakup pelatihan teknik pemasaran, penataan produk, dan penggunaan media sosial untuk promosi. Kegiatan pengabdian dilakukan di pasar tradisional Desa Telaga Waru Lombok Barat dengan menggunakan metode observasi dan wawancara mendalam untuk mengevaluasi dampak program terhadap pedagang yang berpartisipasi. Hasil pengabdian menunjukkan bahwa pelatihan ini berhasil meningkatkan pemahaman dan keterampilan pedagang dalam menerapkan strategi pemasaran yang lebih efektif. Perubahan signifikan terlihat dalam penataan produk yang lebih menarik, peningkatan aktivitas promosi melalui media sosial, serta peningkatan jumlah pelanggan dan penjualan. Selain itu, program ini juga berhasil meningkatkan kesadaran pedagang tentang pentingnya adaptasi terhadap perkembangan teknologi dalam pemasaran. Kesimpulan dari pengabdian ini menekankan perlunya pelatihan berkelanjutan dan dukungan dari pemerintah serta lembaga terkait untuk menjaga keberlanjutan dan daya saing pasar tradisional. Rekomendasi meliputi pengembangan program pelatihan yang lebih komprehensif, penyediaan akses ke sumber daya digital, dan kolaborasi dengan berbagai pihak untuk mendukung keberlanjutan inisiatif ini.